Walking onset: a poor predictor for motor and cognitive skills in healthy preschool children - Nadine Messerli-Bürgy; Tanja H. Kakebeeke; Andrea H. Meyer; Amar Arhab; Annina E. Zysset; Kerstin Stülb; Claudia S. Leeger-Aschmann; Einat A. Schmutz; Susi Kriemler; Jardena J. Puder; Simone Munsch; Oskar G. Jenni (BMC, 2021)
Abstract Background The onset of walking is thought to be an indicator of early development. However, evidence is mixed and clear data on this relationship at preschool age is missing. The study aimed at investigating if walking onset and motor and cognitive development in preschool children are related. Methods A total of 555 children (mean age 3.86 years) of the Swiss Preschoolers' Health Study SPLASHY were tested twice at their childcare center (at baseline and one year later). Motor skills and cognitive skills were assessed by standardized testing procedures and parents were asked to provide information on walking onset of their child. Results Late onset of walking was related to poorer motor skills (fine motor skills, static and dynamic balance (all p < 0.003)) and poorer cognitive skills (selective attention and visual perception (p = 0.02; p = 0.001) in late preschool age. Conclusions For children with late walking onset a close monitoring of their development in the regular pediatric child health visits may be reasonable. Trial registration: ISRCTN41045021 .